Reaction Dynamics of Plant Phenols in Regeneration of Tryptophan from Its Radical Cation Formed via Photosensitized Oxidation - Yuqian Li; Yiming Zhou; Danhong Li; Jianping Zhang (Applied Sciences)
Photooxidation imposes structural damage on proteins, and the amino acid tryptophan (Trp) is a key target for protein oxidation. The Trp radical cation (Trp•⁺), as an oxidative product, can be reduced by plant phenols (φ-OH), a category of dietary phytochemicals essential for human health. This work is intended to investigate the efficacy of φ-OH regeneration of Trp from Trp•⁺ as a function of φ-OH concentration and environmental pH. We have examined, by using laser flash photolysis, six different kinds of φ-OH in the aqueous system consisting of Trp and riboflavin as a photosensitizer. Taking syringic acid (Syr) as an example, upon systematically varying the pH from 2 to 10, the partition of Syr phenolate, Syr-O2−, increases from 0% to 70% and, accordingly, the rate of Trp regeneration increases from 4.8 × 106 M−1·s−1 to 1.7 × 108 M−1·s−1. It is found that the regeneration rate correlates with the driving force of the electron transfer (ET) reaction between φ-OH and Trp•+, which can be well accounted for by Marcus’s ET theory (R² = 0.89). The λ = 0.43 ± 0.08 eV for the reorganization energy for ET from the plant phenols to the Trp•⁺. The effects of φ-OH concentration, environmental pH, and ET driving force on the Trp regeneration reaction herein revealed are significant for enlightening further study of protein (anti)oxidation.